A Comparison of Transcriptional Diversity of Swine Macrophages Infected With TgHB1 Strain of Toxoplasma gondii Isolated in China - Song, Yongle; Song, Lindong; Wan, Xiaoting; Shen, Bang; Fang, Rui; Hu, Min; Zhao, Junlong; Zhou, Yanqin (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii is an apicomplexan parasite infecting human and animals, causing huge public health concerns and economic losses. Swine alveolar macrophage plays an important role in controlling T.gondii infection. However, the mechanism by which macrophages infected with T.gondii function in the immunity to the infection is unclear, especially for local isolates such as TgHB1 isolated in China. RNA-seq as a valuable tool was applied to simultaneously analyze transcriptional changes of pig alveolar macrophages infected with TgRH (typeⅠ), TgME49 (typeⅡ) or TgHB1 at different time points post infection (6 h, 12 h and 24 h). Paired-end clean reads were aligned to the Sscrofa10.2 pig genome and T.gondii ME49 genome. The differentially expressed genes of macrophages and T.gondii were enriched through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes, respectively. Compared to the TgRH and TgME49 infection groups, 307 down-regulated macrophage genes (mainly enriched for development and metabolism) and 419 up-regulated genes (mainly enriched for immune pathways) were uniquely expressed in the TgHB1 infection group. Additionally, 557 down-regulated and 674 up-regulated T.gondii genes (mainly enriched in metabolism and biosynthesis) were uniquely expressed in the TgHB1 infection group. For validation purposes, some of the differentially expressed genes of macrophages involved in immune-related signaling pathways were used for further analysis via real time quantitative reverse-transcription polymerase-chain reaction (real time qRT-PCR). This work provides important insight into the temporal immune responses of swine alveolar macrophages to infection by the strain TgHB1 isolated from China, and is helpful for better understanding of the T.gondii genotype-associated activation of macrophages during early phase of the infection.